My dealings with the aurora borealis - Haerendel, Gerhard (Frontiers in Astronomy and Space Sciences, 2022)
Two important decisions on my career path had the consequence that, after a quarter century of experimentation with barium plasma clouds, I was directing my research more and more towards physics of the auroral borealis. The combination of ground-based optical and radar observations and two national satellite missions were our means to deepen the understanding of the plasma physics background of the aurora, especially of discrete auroral arcs. Our contributions are put in perspective with the global research in this field by a quick run through the major steps in the exploration of the physics of the aurora. Although by the end of the 20th century all key ingredients for the understanding of auroral arcs were available, the present state leaves many open questions, foremost with respect to the true generators processes and the overall flow of momentum and energy. Some of these questions I tried to address during my retirement years.